Tourism, Gentrification, and Social Justice in Jakarta: How Urban Tourism Impacts Lower-Income Communities (Indonesian Tourism Justice Review, 2025)
Urban tourism in Jakarta has contributed to significant economic growth, yet its impacts on lower-income communities are often overlooked. This paper critically examines the social justice implications of gentrification driven by tourism development in Jakarta, focusing on the displacement of marginalized populations from traditionally low-income neighborhoods. The study explores how the development of luxury hotels, shopping malls, and entertainment districts for tourists has led to rising property prices and the displacement of local residents. Using a combination of urban studies theory and social justice frameworks, the paper analyzes the socioeconomic effects of gentrification on housing, employment, and social networks in affected communities. The paper also evaluates the role of local and national government policies in exacerbating or mitigating these impacts. It concludes by offering policy recommendations aimed at addressing the negative consequences of gentrification, such as the implementation of affordable housing initiatives, community land trusts, and the inclusion of local voices in urban tourism planning.